ANALISIS PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BEI - Nugroho Hepi Kuncoro; Bambang Sudiyatno (Fakultas Ekonomi Universitas Pekalongan, 2022)
The purpose of this study is to test the influence of financial performance including current ratio and debt to total assets ratio and return on assets to stock returns, while making return on assets as moderation variable with the size of the company as a control variable. The object of the research is a property and real estate company with an observation period from 2015 to 2019 and has been/listed on the Indonesia Stock Exchange. The source of this research data is secondary data published by the official website of Indonesia Stock Exchange and www.yahoofinance.com. The sampling method is purposive sampling with a total of 180 data from 36 companies during the observation period. Panel data regression and moderated regression analysis (MRA) were used as analytical techniques to test hypotheses in the study, which found that current ratio and debt to total assets ratio had no significant effect on stock returns; return on assets had significant positive effect on stock return;, Moderation 1 (interaction of CR and ROA) had negative significant effect on stock returns; and moderation 2 (DAR and ROA interaction) had no significant effects on stock returns